Impact Motivasi Investasi, Literasi Keuangan, dan Perilaku Keuangan Terhadap Keputusan Investasi - Risa Ratna Gumilang; Helles Amanda; Yayat Ginanjar (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
This study aims to examine the effect of investment motivation, financial literacy and financial behavior on investment decisions. This type of research is quantitative research using descriptive methods. The data processed is primary data obtained from the results of distributing questionnaires with simple random sampling technique to students of the management study program at Sebelas April University. The research sample is 246 respondents. Data analysis was performed using the PLS (Partial Least Square) program. The results of this study indicate that there is a positive and significant influence of investment motivation, financial literacy and financial behavior on investment decisions. Financial literacy needs to be improved so that students are more motivated to make investments and have good finances for the future.